The Influence of Servant Leadership on Employee Performance with Managerial Skills as Mediator - Zulfikar Baharuddin Ibnu Ghazali; Hanif Mauludin (Citakonsultindo, 2025)
This study aims to analyze the influence of servant leadership on employee performance with managerial skills as a mediating variable. The background of this research is based on the importance of a leadership style that serves in creating a productive work environment, especially in Correctional Institutions which have high work challenges. In this context, managerial skills are seen as an important factor in optimizing the influence of leadership on performance. This study uses a quantitative approach with a survey method on prison employees in Malang. The data was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study show that servant leadership has a positive and significant effect on performance. In addition, managerial skills also have a significant influence on performance and mediate the relationship between servant leadership and employee performance. These findings affirm the importance of developing servant leadership and strengthening managerial skills to improve employee performance. The application of a service-oriented leadership style, when accompanied by good managerial skills, is able to create more optimal performance in complex work environments such as prisons.